THE ANALYSIS OF STUDY AND ORIGIN OF TABOO WORDS (Scientific journal of the Fergana State University, 2023)
The article is dedicated to the investigation of the research levels and spheres of taboo words, their theoretical and practical value, as well as their importance in the branch of linguoculturology. This will allow linguists to further familiarize themselves with the theoretical underpinnings and empirical findings of linguoculturology and gives deeper understanding that is still largely confined.